Five Unique Amino Acid Residues of Hemagglutinin (HA) Proteins of Swine Influenza A (H1N1) Detected in 2009 in Jakarta, Indonesia - ANDI YASMON; YULIANTY MUHAYAR; VIVI SETIAWATY; BETI ERNAWATI DEWI; BUDIMAN BELA; FERA IBRAHIM (Indonesian Society for microbiology, 2012)
Nine HA genes of influenza A (H1N1) viruses originating from swine which were detected in 2009 in Jakarta, Indonesia, were characterized in this study. Nasopharyngeal and/or pharyngeal samples were extracted to obtain viral RNA genomes. Amplification of the HA segment was performed by using the reverse transcription-polymerase chain reaction (RT-PCR), and followed by nested PCR in cases of RT-PCR negative. DNA sequencing was performed by using eight overlapping primers. All the Jakarta strains were closely related to vaccine strain A/California/07/2009. Nine amino acid changes were found in the Jakarta strains, and 5 (P100S, S220T, G239D, R240Q, and I338V) of those were unique to all Jakarta strains with respect to strain A/California/07/2009 used to produce vaccine. An I338V substitution was detected in a cleavage site of HA and no amino acid changes were detected in potential sites for N-linked glycosylation. For seven sites (positions 131, 158, 160, 183, 187, 222, and 227) playing an important role in viral attachment to host receptor, none of the expected amino acid changes was detected; however, a S220T substitution close to amino acid 222 was found in all the Jakarta strains. All amino acid changes potentially affect the pathogenicity of the viruses and the efficacy of strain A/California/07/2009 in neutralizing the Jakarta strains.